Modelling the interaction processes between nanoparticles and biomacromolecules of variable hydrophobicity: Monte Carlo simulations1. Issue 4 (30th August 2015) - Carnal, Fabrice; Clavier, Arnaud; Stoll, Serge
<x xml:space="preserve">Abstract</x> The conformational properties and formation of a complex between a weak flexible biomacromolecule chain of variable hydrophobicity and one negatively charged nanoparticle in the presence of explicit counterions are investigated here using Monte Carlo simulations.